2018
DOI: 10.1186/s13045-018-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting WEE1 to enhance conventional therapies for acute lymphoblastic leukemia

Abstract: BackgroundDespite the recent progress that has been made in the understanding and treatment of acute lymphoblastic leukemia (ALL), the outcome is still dismal in adult ALL cases. Several studies in solid tumors identified high expression of WEE1 kinase as a poor prognostic factor and reported its role as a cancer-conserving oncogene that protects cancer cells from DNA damage. Therefore, the targeted inhibition of WEE1 kinase has emerged as a rational strategy to sensitize cancer cells to antineoplastic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 65 publications
1
41
0
Order By: Relevance
“…Few studies have analyzed WEE1 and PKMYT1 expression in hematological malignancies. Our group showed that WEE1 kinase is highly expressed in acute lymphoblastic leukemia (ALL) cell lines and primary cells in comparison with normal hematopoietic cells, and that PKMYT1 is upregulated in relapsed ALL samples compared with nonmalignant hematopoietic cells [ 35 ]. Moreover, we demonstrated that ALL cells are dependent on WEE1 functionality for their survival and proliferation and that PKMYT1 levels may influence the sensitivity to the WEE1 inhibitor AZD-1775 [ 35 ].…”
Section: Wee1 and Pkmyt1 Deregulation In Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have analyzed WEE1 and PKMYT1 expression in hematological malignancies. Our group showed that WEE1 kinase is highly expressed in acute lymphoblastic leukemia (ALL) cell lines and primary cells in comparison with normal hematopoietic cells, and that PKMYT1 is upregulated in relapsed ALL samples compared with nonmalignant hematopoietic cells [ 35 ]. Moreover, we demonstrated that ALL cells are dependent on WEE1 functionality for their survival and proliferation and that PKMYT1 levels may influence the sensitivity to the WEE1 inhibitor AZD-1775 [ 35 ].…”
Section: Wee1 and Pkmyt1 Deregulation In Cancer Cellsmentioning
confidence: 99%
“…Our group showed that WEE1 kinase is highly expressed in acute lymphoblastic leukemia (ALL) cell lines and primary cells in comparison with normal hematopoietic cells, and that PKMYT1 is upregulated in relapsed ALL samples compared with nonmalignant hematopoietic cells [ 35 ]. Moreover, we demonstrated that ALL cells are dependent on WEE1 functionality for their survival and proliferation and that PKMYT1 levels may influence the sensitivity to the WEE1 inhibitor AZD-1775 [ 35 ]. Similar results on the role of WEE1 were obtained in multiple myeloma (MM), acute myeloid leukemia (AML), chronic myeloid leukemia (CML), and chronic lymphocyte leukemia (CLL) [ 36 39 ].…”
Section: Wee1 and Pkmyt1 Deregulation In Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…[165]. For acute lymphocytic lymphoma, a WEE1 inhibitor AZD-1775 is proven to significantly enhance the efficacy of several tyrosine kinase inhibitors, such as imatinib, bosutinib, and ponatinib [168], or similarly, vitamin K1 with sorafenib in treating HCC [151] and antiestrogen fulvestrant with vandetanib in NSCLC.…”
Section: Combination Therapymentioning
confidence: 99%